A Study on Aerodynamic Effect of a Generic Car Spoiler Using Computational Fluid Dynamics (CFD) - Shafee, Lokman Hakim; Sapit, Azwan (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Most of the time, the car normally breaks through the air barrier when a human drives the vehicle. In an undesired condition where the handling and stability of the car can deteriorate as a result of tires losing the traction to the road because of lift, it can be encountered by installing the spoiler. In this research work, the properties of air flow have been investigated around the spoiler where the value of the drag and lift forces and its coefficient has been computed. The research is to distinguish the forces acting on three types of spoiler with a varied angle of attack and subjected to different velocity. Ansys Fluent is utilised to analyse and simulate a computational fluid dynamic (CFD) technique. It can be seen the angle of attack and velocity affected the magnitude of lift and drag force and their coefficient. At velocity = 45 m/s, all spoiler 1, 2 and 3 experienced downforce with lift coefficient at -0.02632, -0.03705 and - 0.08887, respectively. For this kind of spoiler, the adjustment of angle of attack on spoiler 2 at 10° AOA could be ideal in terms of lift and drag coefficient optimization based on the Lift over Drag Ratio recorded at 4.56. The best spoiler design should have the least drag coefficient and considerably higher negative lift coefficient.